1991
DOI: 10.1002/ijc.2910470219
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of five human malignant mesothelioma cell lines derived from pleural effusions

Abstract: Malignant mesothelioma (MM) is an aggressive tumour of the serosal cavities which is associated with exposure to asbestos. Studies of this tumour have been limited by a paucity of well-characterized human MM cell lines. In this study, 5 human MM cell lines were established from pleural effusions of patients with this malignancy. All 5 patients were males with known crocidolite asbestos exposure, who had received no treatment for their disease and in whom the diagnosis was confirmed by cytology, histology and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 22 publications
3
57
0
Order By: Relevance
“…We used a mouse model of mesothelioma (15,17) to assess the role of PD-1-mediated T cell inhibition in natural tumor-induced immune responses (i.e., without additional therapy). First, we evaluated the expression patterns of PD-L1 on AB1-HA mesothelioma cells.…”
Section: Expression Of Pd-l1 By Tumor Cells and In The Tumor Milieumentioning
confidence: 99%
See 2 more Smart Citations
“…We used a mouse model of mesothelioma (15,17) to assess the role of PD-1-mediated T cell inhibition in natural tumor-induced immune responses (i.e., without additional therapy). First, we evaluated the expression patterns of PD-L1 on AB1-HA mesothelioma cells.…”
Section: Expression Of Pd-l1 By Tumor Cells and In The Tumor Milieumentioning
confidence: 99%
“…However, it has recently been shown that CD25 ϩ regulatory T cells are also under the control of PD-1, i.e., PD-L1 blockade enhanced the suppressive function of regulatory T cells (14). Therefore, the objective of the present study was to investigate the role of PD-1 in tumor-induced immunosuppression in a mouse model of malignant mesothelioma (15), in which immunosuppression depends in part on regulatory T cells (16). To study this, we have used the AB1-hemagglutinin (HA) mesothelioma tumor cell line that was obtained by transfecting asbestos-induced AB1 mesothelioma cells (15) with the infuenza virus HA gene as model tumor Ag (17).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Six previously established MM cell lines, JU77, LO68, ONE58, OLD1612, JO38 and GAY2911, were maintained as previously described (5). The cell lines and the patient demographics from which the cell lines were derived are described in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…The human MM cell lines, JU77, LO68, NO36, ONE58 and STY51 were all derived from the pleural fluid of patients with disease (Manning et al, 1991). The human lung adenocarcinoma, A549, and the human colon cancer line HT29 were purchased from the American Type Culture Collection (Manassas, VA).…”
Section: Cell Lines and Tissue Culturementioning
confidence: 99%